The Expansion of Open University Of Malaysia Through International Collaboration - Hazalina Hashim, (ASEAN Journal of Open and Distance Learning, 2017)
Quality of the programmes and recognition of the provider open up opportunities for higher education expansion regardless of location or nationality. This expansion is pertinent to adapt to the growing demand for international education from the changing nature of the global economy and labour market. As such, it is the interest of this paper to discuss how Open University Malaysia expands its higher educational programmes via collaboration with international partners. Additionally, the paper discusses the function of the International Operation office in managing the operational activities and sustainability of the collaboration. Furthermore, a number of challenges that have surfaced in the collaboration are described and addressed for effective operations management. This paper is deemed valuable for all higher education providers who are optimistic about exploring opportunities for expansion through international collaboration. [Abstract by author]